Laboratory evaluation of pesticides on oviposition, egg mortality and feeding deterrence on cashew stem and root borer, Plocaederus ferrugenius L. (Coleoptera: Cerambycidae) - Vasanthi, P.; Raviprasad, T. N. (Journal of Plantation Crops, 2019)
——————–